2016
DOI: 10.1021/jacs.6b08397
|View full text |Cite
|
Sign up to set email alerts
|

Direct C(sp3)–H Cross Coupling Enabled by Catalytic Generation of Chlorine Radicals

Abstract: Here we report the development of a C(sp3)–H cross-coupling platform enabled by the catalytic generation of chlorine radicals by nickel and photoredox catalysis. Aryl chlorides serve as both cross-coupling partners and the chlorine radical source for the α-oxy C(sp3)–H arylation of cyclic and acyclic ethers. Mechanistic studies suggest that photolysis of a Ni(III) aryl chloride intermediate, generated by photoredox-mediated single-electron oxidation, leads to elimination of a chlorine radical in what amounts t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
406
1
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 589 publications
(426 citation statements)
references
References 28 publications
8
406
1
11
Order By: Relevance
“…[10] Moreover, recent reports from the groups of Fu and Peters, Nocera, Molander, and Doyle describing direct photoexcitation of transition-metal catalysts provide elegant demonstrations of this paradigm. [11] Our group has also demonstrated that energy-transfer photosensitization can be used to access triplet excited states of Ni II complexes, specifically in the context of C–O bond formation between carboxylic acids and aryl halides. [10b] A key benefit of this methodology is the separation of light-harvesting and cross-coupling roles between two different transition-metal complexes.…”
mentioning
confidence: 99%
“…[10] Moreover, recent reports from the groups of Fu and Peters, Nocera, Molander, and Doyle describing direct photoexcitation of transition-metal catalysts provide elegant demonstrations of this paradigm. [11] Our group has also demonstrated that energy-transfer photosensitization can be used to access triplet excited states of Ni II complexes, specifically in the context of C–O bond formation between carboxylic acids and aryl halides. [10b] A key benefit of this methodology is the separation of light-harvesting and cross-coupling roles between two different transition-metal complexes.…”
mentioning
confidence: 99%
“…14 Surprisingly, stoichiometric experiments exposing this complex to a variety of oxidant combinations in the presence of alkyltrifluoroborate 13 failed to afford any of the desired coupling product even under prolonged reaction times. The only products observed were THF-adduct 18 (known to be generated under the reaction conditions through C-H abstraction 15 or halide abstraction pathways 16 ) and protodehalogenation. Given these results, it appeared unlikely that the established bipyridyl ligand systems would be broadly applicable to their tertiary counterparts.…”
mentioning
confidence: 99%
“…Recently, our lab [10] and others reported directing group free Csp 3 –H cross-coupling platforms capable of carrying out C–H arylations at room temperature. In contrast to systems reported by MacMillan [11] and Molander [12] , which primarily employ aryl bromides and iodides, our method utilizes aryl chlorides by design.…”
mentioning
confidence: 99%
“…Simultaneously, visible light irradiation of Ir(III) photocatalyst 3 would generate triplet excited *Ir(III) (τ 0 = 2.3 μs, *E 1/2 = 1.21 V vs SCE in MeCN) ( 4 ) which could engage 2 (E P = 0.85 V vs SCE in THF) in photoinduced electron transfer to give presumed Ni(III) intermediate 5 . [10,13] According to our prior studies, [10] photolysis of 5 produces Ni(II) species 6 and a chlorine radical, capable of abstracting a hydrogen atom from 1,3-dioxolane. A concern in developing this reaction was that 1,3-dioxolane has two sets of chemically distinct α-oxy C–H bonds.…”
mentioning
confidence: 99%